The Labour Market Participation of Humanitarian Migrants in Sweden: An Overview - Nahikari Irastorza; Pieter Bevelander (Intereconomics, 2017)
The aim of this article was twofold: first, to provide an overview of immigration and integration policies in Sweden, and second, to analyse the labour market integration of humanitarian migrants who arrived in Sweden between 1998 and 2012 relative to other migrants and natives.
Keywords: 330